ANTI-VIOLENCE EDUCATION IN THE QUR'AN - Irwansyah Suwahyu; Muhammad Chirzin (Teladan: Jurnal Pendidikan Umum dan Karakter, 2026)
This study aims to examine the concept of anti-violence in the Qur'an, identify the educational values embedded within it, and formulate a conceptual model that can be implemented in contemporary Islamic education systems. This research uses a qualitative approach with library research through the thematic exegesis method (maudhu'i). The primary data consist of the Qur'an, while the secondary data include tafsir works and relevant scholarly literature. The analysis was conducted through the stages of verse identification, thematic classification, interpretation, and synthesis of educational values using source triangulation to ensure validity. The findings show that the Qur'an provides a comprehensive framework for building an anti-violence paradigm that includes the principles of rahmah (compassion), justice ('adl), protection of life (hifz al-nafs), self-control, and conflict resolution based on islah. These values are then formulated into a three-level conceptual model, namely foundational values, mechanisms of individual internalization, and the education system as an implementative ecosystem. This model emphasizes that anti-violence education must be understood as an integrative process that connects values, individual awareness, and the structure of the education system. The implications of this study indicate the need to transform the paradigm of Islamic education from a normative approach toward a value-based transformative approach, implemented through curriculum integration, dialogical pedagogy, teacher exemplarity, and the strengthening of an inclusive and violence-free institutional culture. This study contributes to the formulation of a Qur'an-based conceptual framework for anti-violence education that is relevant to the challenges of contemporary education.